Comparative assessment of shear bond strength and adhesive remnant scores of orthodontic adhesive containing copper-substituted hydroxyapatite nanoparticles with conventional orthodontic adhesive: An in vitro study - Kavitha Ramsundar; Remmiya Mary Varghese; Nivethigaa Balakrishnan; Aravind Kumar Subramanian (Journal of Orthodontic Science, 2025)
BACKGROUND: An ideal orthodontic adhesive should provide a bond strong enough to withstand the forces of orthodontic treatment and mastication without dislodging, while also being safe enough to prevent surface damage debonding. Shear bond strength (SBS) is a critical factor that determines the quality of bonding in orthodontics. Nanoparticle-enhanced adhesives have been reported to offer additional benefits such as antimicrobial properties and remineralization effects, making them worth investigating for their shear bond characteristics. Aim: This in vitro study aimed to evaluate and compare the SBS and Adhesive Remnant Index (ARI) scores of orthodontic adhesives containing copper-substituted hydroxyapatite (Cu-HA) nanoparticles with a conventional orthodontic adhesive. MATERIALS AND METHODS: Twenty-eight extracted human premolar teeth were randomly divided into two groups of 14. In Group 1, orthodontic brackets were bonded using Enlight adhesive mixed with Cu-HA nanoparticles, while Group 2 used conventional Enlight adhesive. SBS was measured using a Universal Testing Machine, and the debonded samples were evaluated for ARI scores under scanning electron microscopy (SEM). Statistical analyses were performed using independent t-tests for SBS comparison and Mann-Whitney U tests for ARI score differences. A P value < 0.05 was considered statistically significant. RESULTS: The group using Enlight adhesive with Cu nanoparticles exhibited a significantly higher mean SBS (9.03 ± 6.17 MPa) compared to the conventional adhesive group (5.51 ± 2.099 MPa, P = 0.003). The median ARI score for the Cu-HA nanoparticle group was 3, while the conventional group had a median ARI score of 2 (P = 0.022). Both SBS and ARI scores were significantly higher in the Cu-HA nanoparticle group. CONCLUSION: Copper-substituted hydroxyapatite nanoparticles enhance bond strength and adhesive retention, making them a promising alternative to conventional adhesives in orthodontics. CLINICAL RELEVANCE: The findings indicate that adhesives containing Cu-HA nanoparticles, especially when combined with the Enlight adhesive, offer superior bond strength and adhesive retention compared to conventional adhesives. This could lead to improved clinical outcomes in orthodontic bonding, potentially reducing bracket failure rates and enhancing treatment efficiency.